2014
DOI: 10.3389/fneur.2014.00047
|View full text |Cite
|
Sign up to set email alerts
|

Blast TBI Models, Neuropathology, and Implications for Seizure Risk

Abstract: Traumatic brain injury (TBI) due to explosive blast exposure is a leading combat casualty. It is also implicated as a key contributor to war related mental health diseases. A clinically important consequence of all types of TBI is a high risk for development of seizures and epilepsy. Seizures have been reported in patients who have suffered blast injuries in the Global War on Terror but the exact prevalence is unknown. The occurrence of seizures supports the contention that explosive blast leads to both cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 95 publications
(132 reference statements)
2
63
0
Order By: Relevance
“…In summary, it was found that a single blast exposure was sufficient to cause brain pathology and memory impairment. This finding replicates the findings of Kovesdi and colleagues, conducted in an F344 rat model (Kovesdi et al, 2011).…”
Section: Chronic Traumatic Encephalopathysupporting
confidence: 94%
See 2 more Smart Citations
“…In summary, it was found that a single blast exposure was sufficient to cause brain pathology and memory impairment. This finding replicates the findings of Kovesdi and colleagues, conducted in an F344 rat model (Kovesdi et al, 2011).…”
Section: Chronic Traumatic Encephalopathysupporting
confidence: 94%
“…The sequela of bTBI can be temporary or chronic. Posttraumatic epilepsy (PTE) may also develop in 10%-25% of closed head TBI cases and in 50% of those with a penetrating head injury (Kovacs et al, 2014). The risk for developing PTE is correlated to the severity of TBI.…”
Section: Blast Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…[102][103][104] The observed microglial activation is likely to have occurred via their Toll-like 4 receptors in response to small soluble factors (e.g., glutamate, ATP) and/or debris (e.g., cytoskeletal elements, proteolytic breakdown products, and lipid) released by or associated with damaged axons, their terminals, and the associated myelin. 105,106 Many authors have suggested that persistent microglial activation initiates an inflammatory cascade that worsens the outcome after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Because TBI results from the exposure of military personnel to explosive detonations during modern warfare [5][6][7][8][9]-largely due to IEDs-there is a considerable need for further research in this area. This is to explain, and ultimately mitigate against, the negative consequences of harmful brain trauma, as well as possible mental and psychological disorders that often result.…”
Section: Neurological Shock-wave Dynamics Explainedmentioning
confidence: 99%